Improving Students Dokkai (Reading Comprehension) Performance Through Correlation Analysis of Cognitive Anxiety and Japanese Reading Understanding - Prasetya, Dany Buyung Yudha; Setiawati, Ai Sumirah; Asrini, Dwi Puji; Puspitosari, Dwi (Universitas Pendidikan Ganesha, 2025)
Reading ability, known as Dokkai in Japanese, is one of the problematic parts of the Japanese Language Proficiency Test. The problem in this study focuses on the low performance of students in understanding Japanese reading (Dokkai). This study examines cognitive anxiety and its correlation with the results of the Dokkai test of Japanese language learners. The Cognitive Test Anxiety Scale (CTAS) was used to survey learners' cognitive anxiety level, and the final semester exams of two courses related to Dokkai were used to obtain Dokkai test scores. CTAS responses and scores from the exam results were then analyzed using SPSS. This study used a quantitative research design to determine the relationship between variables. The population of this study was first-year students (second semester) registered in the Japanese Language Education Study Program, totaling 90 people. A random study used a Random sampling technique, considering the population's homogeneous nature. The respondents of this study were 58 first-year Japanese language students, consisting of 25 males and 33 females. The results of the study showed that students experienced a moderate level of cognitive anxiety when facing the Dokkai test, which was manifested physically and affected the cognitive process. The results of the analysis showed that there was a low negative correlation between CTAS and the results of the two Dokkai tests. The implications of this study have a significant effect on the ability to understand texts, so teachers and educators need to design a teaching approach that not only focuses on linguistic aspects but also pays attention to the psychological conditions of students.